Functional Groups and Ionic Conductivity of Chitosan/LiOH/ZnO Membranes for Secondary Batteries - Sari, Kartika; Setiabudi , Angga; Halifah , Rofikoh; Lumban Toruan, Parmin (Jurnal Penelitian Fisika dan Terapannya (JUPITER), 2025)
The development of solid-state electrolytes with high ionic conductivity and structural stability is crucial for advancing secondary battery technologies. Solid electrolytes play a critical role in facilitating ion transfer between electrodes, directly impacting battery efficiency. Solid electrolyte polymer membranes can be manufactured for use in secondary batteries as electrical energy storage devices. In batteries, solid electrolytes act as a medium for ion transfer. The polymer membrane was modified by incorporating Zinc Oxide (ZnO) into the chitosan/LiOH polymer membrane using the solution casting method. Fourier Transform Infrared (FTIR) and Electrochemical Impedance Spectroscopy (EIS) tests were conducted. The FTIR analysis of the polymer membrane revealed the presence of functional groups such as OH stretching, -NH stretching, -NH bending, -CO stretching, -CH stretching, and -ZnO stretching. The EIS results demonstrated that the ionic conductivity of the 3% chitosan/LiOH/ZnO membrane was higher at 1.4821 x 10-6 S/cm compared to the 2% chitosan/LiOH/ZnO membrane at 3.6893 x 10-7 S/cm. This study suggests that chitosan/LiOH membranes doped with Zinc Oxide (ZnO) are a promising option for solid electrolyte membranes in secondary batteries